2004
DOI: 10.1158/1078-0432.ccr-04-0076
|View full text |Cite
|
Sign up to set email alerts
|

BNIP3 Expression Is Linked with Hypoxia-Regulated Protein Expression and with Poor Prognosis in Non–Small Cell Lung Cancer

Abstract: BNIP3 is a proapoptotic protein regulated by hypoxiainducible factor 1. We analyzed BNIP3 expression in 105 tumor samples from early operable, non-small lung cancer and the relationship of expression to hypoxia-inducible factor 1␣, other hypoxia-regulated pathways, and prognosis. There was strong cytoplasmic expression in >10% of cells in 40 of 105 cases. BNIP3 expression was associated significantly with high hypoxia-inducible factor 1␣ (P ‫؍‬ 0.003), carbonic anhydrase 9 (P ‫؍‬ 0.04), and was inversely assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
131
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(146 citation statements)
references
References 15 publications
10
131
0
5
Order By: Relevance
“…In 10 of the matched pairs, BNIP3 was higher in the tumour sample than in the normal (Figure 2a and b) as shown in other tumour types (Sowter et al, 2003;Giatromanolaki et al, 2004). However, in 54 cases, BNIP3 expression was reduced in the tumour samples relative to the normal, indicating that there had been a loss of BNIP3 expression during cancer development (Figure 2c and d).…”
Section: Bnip3 Expression In Matched Normal and Tumour Pairsmentioning
confidence: 77%
See 3 more Smart Citations
“…In 10 of the matched pairs, BNIP3 was higher in the tumour sample than in the normal (Figure 2a and b) as shown in other tumour types (Sowter et al, 2003;Giatromanolaki et al, 2004). However, in 54 cases, BNIP3 expression was reduced in the tumour samples relative to the normal, indicating that there had been a loss of BNIP3 expression during cancer development (Figure 2c and d).…”
Section: Bnip3 Expression In Matched Normal and Tumour Pairsmentioning
confidence: 77%
“…Other mechanisms to by-pass the effects of BNIP3 have been shown, for example, growth factor signalling can protect against BNIP3-mediated cell death in breast cancer cell lines (Kothari et al, 2003). There is also evidence that nuclear sequestration may act as a mechanism of BNIP3 silencing in non-small-cell lung cancer (Giatromanolaki et al, 2004). Taken together, the data presented here along with recent studies support a model whereby hypoxic upregulation of BNIP3 in tumour development can cause significant hypoxia-induced cell death, but that this negative function provides pressure for the selection of cells that evade this phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These markers were shown to correlate for both primary breast tumours and lymph node metastases [53], and further studies have demonstrated reduced survival correlated with CA IX expression in breast cancer [54]. In breast cancer, high BNIP3 expression was associated with good survival outcome in invasive carcinoma but with an increased risk of recurrence and shorter disease-free survival in ductal carcinoma in situ [55], while in non-small lung cancer, high expression was an independent factor for overall survival [56]. Further investigation is required to obtain a better appreciation of the value of HIF or HIF-related marker immunohistochemistry for prognosis.…”
Section: Clinical Significance Of Hypoxia Hif and Hif Downstream Genmentioning
confidence: 97%